Hukum Jual Beli COD (Cash On Delivery) dalam Hukum Islam - Makmuriyah, Makmuriyah (Medan Resource Center, 2023)
This article discusses the practice of Cash On Delivery (COD) in Islamic law, emphasizing the importance of conducting business in accordance with Islamic principles. It explores the concept of COD in the context of online business and its advantages and disadvantages. The article provides the legal basis for buying and selling in Islam, including references from the Quran, Hadith, and consensus of scholars. It highlights the importance of certainty in goods, proper payment, agreed-upon prices, and clear rules and regulations in COD transactions. The article also emphasizes the principles of justice, honesty, trust, and certainty in business transactions in Islam. It concludes that COD is permissible in Islam as it is a safe method that allows for the verification of the authenticity of goods.